2020
DOI: 10.1038/s41389-020-00275-x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Chk1 by miR-320c increases oxaliplatin responsiveness in triple-negative breast cancer

Abstract: Checkpoint kinase 1 (Chk1) expression is enhanced in most cancers owing to oncogenic activation and constant replicative stress. Chk1 inactivation is a promising cancer therapy, as its inactivation leads to genomic instability, chromosomal catastrophe, and cancer cell death. Herein, we observed that miR-320c, downregulated in triple-negative breast cancer (TNBC) patients, can target Chk1. In addition, downregulated miR-320c expression was associated with poor overall survival in TNBC patients. As Chk1 was asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…The downregulation of miR-320 has been reported to be relevant to drug resistance to treatments such as oxaliplatin, epirubicin, gemcitabine, tamoxifen, and doxorubicin [ 34 , 77 , 85 , 86 , 87 , 88 , 89 ]. However, the drug resistance mechanisms utilized in these examples are not fully understood.…”
Section: Tumor Suppressive Functions Of Mir-320mentioning
confidence: 99%
See 2 more Smart Citations
“…The downregulation of miR-320 has been reported to be relevant to drug resistance to treatments such as oxaliplatin, epirubicin, gemcitabine, tamoxifen, and doxorubicin [ 34 , 77 , 85 , 86 , 87 , 88 , 89 ]. However, the drug resistance mechanisms utilized in these examples are not fully understood.…”
Section: Tumor Suppressive Functions Of Mir-320mentioning
confidence: 99%
“…However, the drug resistance mechanisms utilized in these examples are not fully understood. Interestingly, some reports have found that the recovery of miR-320 expression can effectively alleviate drug resistance to certain drugs [ 34 , 77 , 88 ]. For example, Wan et al [ 34 , 63 ] reported that overexpression of miR-320 could elevate the sensitivity of CRC cells to 5-Fu and oxaliplatin by targeting forkhead box M1 (FOXM1) .…”
Section: Tumor Suppressive Functions Of Mir-320mentioning
confidence: 99%
See 1 more Smart Citation
“…In different blood samples or solid tumour tissues, miRNAs show a high degree of specificity and are closely related to clinical aspects, such as the survival time of tumour patients, drug sensitivity and mRNA expression. A number of studies have found that miRNAs have an inevitable connection with the occurrence and development of BC 8‐10 . This indicates that miRNAs have important regulatory functions.…”
Section: Introductionmentioning
confidence: 99%
“…As a third-generation platinum compound, oxaliplatin (OX) exerts its anti-tumor effect by disrupting DNA synthesis and is even effective in cells resistant to cisplatin and carboplatin [ 5 ]. Moreover, OX also showed its anticancer function in BC chemotherapy [ 6 ]. Hence, to discover novel targets for treatment and improve the prognosis of BC patients, it is reasonable to explore the underlying mechanism of OX resistance in BC.…”
Section: Introductionmentioning
confidence: 99%